Polymorphisms in immunosuppression-related genes are associated with AML - Mingying Li; Mingying Li; Jingjing Ye; Jingjing Ye; Mengyuan Chang; Mengyuan Chang; Lei Feng; Lei Feng; Tingting Liu; Tingting Liu; Di Zhang; Di Zhang; et al. (Frontiers in Immunology)
BackgroundAcute myeloid leukemia (AML) is a hematologic malignancy with poor overall survival (OS). The immunosuppressive microenvironment significantly impacts AML development and chemoresistance. Despite new immunotherapeutic strategies entering standard clinical care for various tumors, progress in AML remains poor. Multi-omics analyses, such as single-cell transcriptomics, have revealed many potential new targets to improve AML prognosis from an immunological perspective.MethodsDNA from 307 AML patients and 316 healthy individuals were extracted. We detected nine single nucleotide polymorphisms (SNPs) in five immunosuppression-related genes (CIITA, CD200, CD163, MRC1 and LILRB4) in these samples. SNP genotyping was performed on the MassARRAY platform. We then analyzed the relationship between these SNPs and AML susceptibility, treatment response, and prognosis.ResultsOur findings indicated that rs4883263 in the CD163 gene is a protective factor for AML susceptibility and chromosomal karyotype abnormalities. Additionally, rs4883263 in CD163 was related to low PLT count at diagnosis, while rs2272022 in CD200 was protective against low PLT count. rs4780335 in CIITA was associated with high WBC count at diagnosis and worse OS. Furthermore, rs1048801 in LILRB4 was linked to worse AML treatment response, lower OS, and may be an independent prognostic risk factor for AML. Lastly, expressions of CD163, CIITA, LILRB4, and CD200 were higher in AML patients than that in normal controls.ConclusionsOur findings on SNP associations in AML immunosuppression-related genes provide important reference points for predicting treatment outcomes in AML patients.